Multiple Primary Lung Cancers With ALK Rearrangement: A Case Report and Literature Review - Huimin, Zhou; Xueting, Wang; Qi, Qi; Lingxin, Feng; Xue, Yang; Zhuang, Yu; Jing, Wang (Frontiers in Oncology, 2022)
Multiple primary lung cancers (MPLCs) are that patients with lung cancer may present with two primary tumors at the same time (synchronous multiple primary lung cancer, SMPLC) or may develop a second, metachronous primary lung cancer after treatment of the initial lesion. Currently, there are no definitive guidelines for the diagnosis and treatment of multiple primary lung cancers. Herein, we report a case of double primary lung cancers with ALK rearrangement. The patient was treated with chemotherapy, targeted therapy, and radiotherapy. After these treatments, the patient was free of locally recurrent or distant disease at 2 years.